Body area network transfer function measurement with frequency band from 3 GHz to 9 GHz - Chaisang, Aditep; Promwong, Sathaporn (My University, 2019)
Wireless technology for body area network (BAN) is significant interesting in the modern development of short range wireless communication network. Impulse characterization of ultra-wideband is important parameter that used to study in order to understand a signal propagation of BAN channel. Since the complexity of wireless human body applications are higher than another application. Anyway, it is important to understand the channel distribution characteristics due to human body effect. In this research report, transfer function of BAN channel at frequency 3-9 GHz have been presented as the characteristics of waveform transmission in case of with and without human body for apply to the development of short range wireless applications based on the measurement data of this report. To obtain the maximum value of signal to noise ratio (SNR), the matched filter was used as the optimum receiver for better signal quality and well evaluation of BAN system. The transmission equation of Friis was introduce to evaluate the measurement results in this report. The proposed method provides a higher precision and useful for the analysis and design of BAN channel to apply with the system of wireless medical system which focusing on the distortion of transmission signal.
Keywords: BAN; Delay time; Path loss; UWB; WBAN